Outcome and predictive factors in post-stroke seizures: A retrospective case-control study. (November 2018) - Castro-Apolo, Ramiro; Huang, Josephine F.; Vinan-Vega, Myrian; Tatum, William O.
Highlights: Ischemic stroke is the most common cause of seizures in the elderly. Larger stroke size in the anterior cerebral circulation correlated with new-onset seizures. Laminar necrosis and/or hemosiderin deposits constitute significant risks to develop post-stroke seizures. Post-stroke seizures patients have worse short and long-term outcomes according to the mRS. Abstract: Purpose: To evaluate clinical, radiographic, and electrophysiological features in the development and prognosis of ischemic post-stroke seizures (PSS). Method: A retrospective study of 1119 patient records was performed between January 2006 and December 2016. After selection, 42 patients with seizures due to ischemic stroke were matched to a control group of 60 patients where seizures were absent. Stroke size and severity were analyzed using ASPECTS and NIHSS, respectively. Hemorrhagic transformation graded by ECASS III classification. Outcomes were assessed using the modified Rankin Scale. Fisher's exact test assessed categorical variables, and Mann-Whitney tested continuous variables. Results: Forty-two patients experienced PSS (22 females; median age 72.5 years) and were matched with 60 control subjects that had ischemic stroke without seizures. Focal seizures were present in 42.9% (18/42), and focal to bilateral convulsions in 57.1% (24/42). Stroke localization and severity did not differ (p = 0.6 and 0.21, respectively). Stroke size in anterior circulation was larger in PSS patients (median ASPECTS 6 vs 8 [ p = 0.01 ]). Posterior circulation stroke size was similar in both groups. The presence of hemorrhage was the primary risk factor for PSS (61.9%) compared to controls (36.7%), p = 0.01 . The presence of laminar necrosis (LN) (47.6% vs 21.6%, p = 0.005 ) and hemosiderin deposition (38.1% vs 18.3%, p = 0.02 ) were most predictive. PSS patients demonstrated worse outcomes than the controls (median mRS 3 vs 2, [ p=<0.001 ]) with a median follow up of 14.8 and 20.7 months, respectively. Conclusions: The size of anterior infarction, presence of blood products within the infarct bed, and especially LN predicted PSS.